Toward neural health measurements for cochlear implantation: The relationship among electrode positioning, the electrically evoked action potential, impedances and behavioral stimulation levels - Lambriks, Lars; van Hoof, Marc; Debruyne, Joke; Janssen, Miranda; Hof, Janny; Hellingman, Katja; Devocht, Elke; George, Erwin (Frontiers in Neurology, 2023)
Introduction Estimating differences in neural health across different sites within the individual cochlea potentially enables clinical applications for subjects with a cochlear implant. The electrically evoked compound action potential (ECAP) is a measure of neural excitability that possibly provides an indication of a neural condition. There are many factors, however, that affect this measure and increase the uncertainty of its interpretation. To better characterize the ECAP response, its relationship with electrode positioning, impedances, and behavioral stimulation levels was explored. Methods A total of 14 adult subjects implanted with an Advanced Bionics cochlear electrode array were prospectively followed up from surgery to 6 months postoperative. Insertion depth, distance to the modiolus, and distance to the medial wall were assessed for each electrode by postoperative CT analysis. ECAPs were measured intraoperatively and at three visits postoperatively on all 16 electrodes using the NRI feature of clinical programming software and characterized using multiple parameters. Impedances and behavioral stimulation levels were measured at every fitting session. Results Patterns in ECAPs and impedances were consistent over time, but high variability existed among subjects and between different positions in the cochlea. Electrodes located closer to the apex of the cochlea and closer to the modiolus generally showed higher neural excitation and higher impedances. Maximum loudness comfort levels were correlated strongly with the level of current needed to elicit a response of 100 μV ECAP. Conclusion Multiple factors contribute to the ECAP response in subjects with a cochlear implant. Further research might address whether the ECAP parameters used in this study will benefit clinical electrode fitting or the assessment of auditory neuron integrity.